Hematological indications for the treatment of fractures of tubular bones in dogs by osteosynthesis - S.A. Khaidarova (Genius Journals, 2022)
The paper presents the results of studies to determine the morphological and biochemical parameters in the blood of dogs with fractures of tubular bones during treatment according to a special treatment regimen after intramedullary osteosynthesis
Keywords: Tubular bones; intramedullary osteosynthesis; hemoglobin; erythrocytes